Physical activity to improve strength and balance in old people - Chalapud Narváez, Luz Marina; Escobar Almario, Armando Edison (Universidad y Salud, 2017)
Introduction: Old age encompasses a fairly broad age in a person’s life, and physical activity becomes the strategy to improve the elderly’s life quality. Objective: To determine the effectiveness of a physical activity program in improving strength to the lower limbs and balance for the elderly. Materials and methods: Semi-experimental longitudinal study with a sample of 57 elderly people to whom an initial and final assessment of balance and strength was performed, as well as a 4-week physical activity program with 2 training sessions each, comprising posture, proprioception, balance and muscle strength exercises. The program used for data analysis was SPSS v.24.0 for Windows. An univariate analysis was performed applying central trend measurements (mean, median, mode, standard deviation, range) and a statistical analysis with non-parametric testing for two related Wilcoxon samples. Results: The following tests showed statistical significance: Functional extension (p=0,000), open eyes tandem (p=0,20), closed eyes tandem (p=0,002), closed eyes unipodal (p=0,012) and sitting/standing (p=0,000). Conclusion: This study determined that physical activity is effective to improve balance and muscle strength for lower limbs and a suitable tool to preserve senior’s functionality and Independence.